Evaluating the fillet quality and sensory characteristics of Atlantic salmon (Salmo salar) fed black soldier fly larvae meal for whole production cycle in sea cages - Radhakrishnan, Gopika; Philip, Antony Jesu Prabhu; Caimi, Christian; Lock, Erik Jan Robert; Araujo, Pedro; Liland, Nina Sylvia; Rocha, Celia; Cunha, Luís Miguel; Gasco, Laura; Belghit, Ikram (Aquaculture Reports, 2024)
There is scarce research on the use of black soldier fly larvae (BSFL) meal in the diets of Atlantic salmon (Salmo salar) reared in a real farm. Thus, the current study aimed to evaluate the effect of feeding BSFL meal to salmon in terms of fillet quality and sensory analysis at farm level conditions. Fish were fed a total of three diets (pellet size; 4.5 mm and 9 mm); a control diet (Control: 0% BSFL meal) formulated using a standard commercial recipe, containing FM (10%) and plant-based proteins. Two experimental diets were formulated using partially defatted BSFL meal (53% crude protein), in which plant-based proteins at 37% inclusion level from the control diet (4.5 mm pellets) were replaced by BSFL meal at 5% (BSFL 5%) and 10% (BSFL 10%). While for the 9.0 mm pellets, plant-based proteins at 35% were replaced by the BSFL meal at 5% and 10% inclusion level. All the three diets were formulated to be iso-nitrogenous and iso-lipidic diets. Diets were assigned to the sea-cages in triplicate (12 ×12 m; 1900 m3); housing ∼6000 fish per cage from 173 ± 2.7 g to harvest size 3.45 ± 74 kg for a period of 13 months. Feeding salmon with BSFL meal had no negative impact on the general fillet physical, chemical, and nutritional parameters. The fillet sensory evaluation showed that the control samples were associated with the typical attributes such as fresh salmon taste, while BSLF 10% to rancid taste but these attributes were not significantly different among the dietary groups. Overall, the current study showed that diet containing BSFL meal did not affect the general fillet parameters compared to salmon fed a commercial diet and thus validate the inclusion of BSFL meal up to 10% reared for a whole production cycle in sea cages. publishedVersion